A Roman province in the mirror of pop-culture - D. V. Kiryukhin; A. S. Kuprin (Шаги)
A review of: Baryshnikov, A. (2023). Rimskaia Britaniia : 12 lektsii dlia proekta Magisteriia [Roman Britain : 12 lectures for the Magisteria project]. Rosebud Publishing. 516 p. (In Russian).